Penetrating Ballistic-Like Brain Injury Leads to MicroRNA Dysregulation, BACE1 Upregulation, and Amyloid Precursor Protein Loss in Lesioned Rat Brain Tissues - Thangavelu, Bharani; Wilfred, Bernard S.; Johnson, David; Gilsdorf, Janice S.; Shear, Deborah A.; Boutté, Angela M. (Frontiers in Neuroscience, 2020)
Severe traumatic brain injury (TBI) is a risk factor for neurodegenerative diseases. Yet, the molecular events involving dysregulated miRNAs that may be associated with protein degradation in the brain remains elusive. Quantitation of more than 800 miRNAs was conducted using rat ipsilateral coronal brain tissues collected 1, 3, or 7 days after penetrating ballistic-like brain injury (PBBI). As a control for each time-point, Sham-operated animals received craniotomy alone. Microarray and systems biology analysis indicated that the amplitude and complexity of miRNAs affected were greatest 7 day after PBBI. Arrays and Q-PCR inferred that dysregulation of miR-135a, miR-328, miR-29c, and miR-21 were associated with altered levels of beta-site amyloid precursor protein cleaving enzyme 1 (BACE1), PSEN1, PSEN2, and amyloid precursor protein (APP) genes. These events were followed by increased levels of mature BACE1 protein and concomitant loss of full length APP within 3–7 days, then elevation of amyloid beta (Aβ)-40 7 days after PBBI. This study indicates that miRNA arrays, coupled with systems biology, may be used to guide study design prior validation of miRNA dysregulation. Associative analysis of miRNAs, mRNAs, and proteins within a proposed pathway are poised for further validation as biomarkers and therapeutic targets relevant to TBI-induced APP loss and subsequent Aβ peptide generation during neurodegeneration.